Maximal O2 Uptake Is Higher During Whole-Body Compared to Lower-Body Exercise due to Higher Convective, but not Diffusive, O2 Transport - Elias M. A. Lehtonen; Juha E. Peltonen; Antti-Pekka E. Rissanen; Virpi Rajala; Tom Mikkola; Dominique D. Gagnon (Medicine & Science in Sports & Exercise, 2026)
Purpose: Maximal O 2 uptake (V̇O 2max ) is higher during whole-body compared to lower-body large muscle mass exercise. However, whether this is explained by differences in convective or diffusive O 2 transport is unclear. We examined differences in components of the O 2 pathway and muscle tissue (de)oxygenation between whole-body (uphill walking/running with ski poles) and lower-body (cycling) exercise in 14 Tier 3 male triathletes. Methods: Participants completed ramp-incremental tests to exhaustion in both modalities. We assessed systemic O 2 transport via ergospirometry, pulse oximetry, impedance cardiography and hemoglobin concentration. Muscle oxygenation (vastus lateralis) was monitored using near-infrared spectroscopy. We modeled convective (Q̇aO 2max ) and diffusive (ḊO 2max ) O 2 transport at maximal exercise using the Helsinki O 2 Pathway Tool. The slopes for convective O 2 flow (Q̇aO 2slope ) and arterial mixed-venous O 2 content (C(a - v)O 2slope ) were determined against O 2 uptake (V̇O 2 ). Results: V̇O 2max and Q̇aO 2max were higher during whole-body than lower-body exercise (mean [95%CI]: 5.07 [4.83–5.31] versus 4.70 [4.4–4.95] L/min, q = 0.0002, and; 6.02 [5.61–6.43] versus 5.39 [4.96–5.82] L/min, q = 0.0004, respectively). ḊO 2max did not differ between whole-body (147 [113–181] ml/min/mmHg) and lower-body (169 [130–208] ml/min/mmHg) exercise (q = 0.184). Q̇aO 2 was higher and C(a - v)O 2 lower as a function of V̇O 2 during whole-body than lower-body exercise. Peak amplitudes of total- and deoxygenated hemo- and myoglobin were lower during whole-body compared to lower-body exercise (q = 0.002 and q = 0.0005, respectively), but tissue saturation index was unchanged (q = 0.453). Conclusions: V̇O 2max was higher during whole-body compared to lower-body exercise due to higher convective, but not diffusive O 2 transport. Throughout incremental exercise, V̇O 2 relied more on Q̇aO 2 during whole-body compared to lower-body exercise.